The evaluation of procedures for dyeing silk with buckthorn and walloon oak on the basis of colour changes and fastness characteristics - (:unkn) unknown (WILEY, 2013)
In this study, silk fabric samples were dyed according to various procedures with buckthorn (Rhamnus petiolaris Boiss) and walloon oak (Quercus ithaburensis Decaisne) extracts. Reversed-phase high-performance liquid chromatography with diode-array detection was utilised for the identification of dyes present in the dyed silk fabrics and the plant extracts. The extraction of dyes was carried out with a hydrochloric acid/methanol/water (2:1:1; v/v/v) mixture. The colour coordinates of the silk fabrics were measured, and the rubbing, wash and light fastness properties of the dyed silk materials were determined and are discussed.
Keywords: RP-HPLC-DAD; QUERCUS-ITHABURENSIS DECAISNE; DIODE-ARRAY DETECTOR; NATURAL DYES; HISTORICAL TEXTILES; LIQUID-CHROMATOGRAPHY; LC-MS; IDENTIFICATION; PIGMENTS; DYESTUFFS